2020
DOI: 10.1021/acs.iecr.0c00119
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Structure, and Dynamic Properties of Nanostructured Water Confined into B-, N-, and Si-Doped Graphene Surfaces and Carbon Nanotubes

Abstract: The properties of water molecules in nanoconfined geometries have significant roles in different fields such as adsorption, electrochemistry, biology, earth science, materials science, and nanofluidic devices. In this work, water molecules confined between parallel graphene plates and also confined into carbon nanotubes (CNTs) doped with (3 and 20%) B, N, and Si atoms have been studied using molecular dynamics (MD) simulations. Some structural, thermodynamics, and dynamical properties of the water molecules we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Regarding the viscosity and flow of water in nanochannels, after pioneering computational work describing the enhanced flow of water through a CNT, there have been many more recent studies disclosing surprising dynamical properties of water in nanoconfinement. Overall, they consolidate the view that water confined in graphene slit pores and CNTs shows an extremely low resistance to flow with respect to the respective carbon walls, in stark contrast to what can be seen in geometrically equivalent structures composed of different constituents like boron nitride . Along these lines, some efforts toward understanding the structure and dynamics of water at confinement materials subject to substitutions, such as B-, N-, or Si-doped graphene and CNTs, are beginning to appear . In addition, recent computational work describes that the shear viscosity of confined water between two graphene layers which are separated by interlayer distances ranging from 7 to 20 Å may oscillate by as much as several orders of magnitude depending on the precise slit width (Figure ).…”
Section: Nanoconfinement Effects On Water: Setting the Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the viscosity and flow of water in nanochannels, after pioneering computational work describing the enhanced flow of water through a CNT, there have been many more recent studies disclosing surprising dynamical properties of water in nanoconfinement. Overall, they consolidate the view that water confined in graphene slit pores and CNTs shows an extremely low resistance to flow with respect to the respective carbon walls, in stark contrast to what can be seen in geometrically equivalent structures composed of different constituents like boron nitride . Along these lines, some efforts toward understanding the structure and dynamics of water at confinement materials subject to substitutions, such as B-, N-, or Si-doped graphene and CNTs, are beginning to appear . In addition, recent computational work describes that the shear viscosity of confined water between two graphene layers which are separated by interlayer distances ranging from 7 to 20 Å may oscillate by as much as several orders of magnitude depending on the precise slit width (Figure ).…”
Section: Nanoconfinement Effects On Water: Setting the Stagementioning
confidence: 99%
“…51 Along these lines, some efforts toward understanding the structure and dynamics of water at confinement materials subject to substitutions, such as B-, N-, or Si-doped graphene and CNTs, are beginning to appear. 56 In addition, recent computational work 57 describes that the shear viscosity of confined water between two graphene layers which are separated by interlayer distances ranging from 7 to 20 Å may oscillate by as much as several orders of magnitude depending on the precise slit width (Figure 4). Within this context, it must be noted that the flow of the fluid through a nanochannel is not only determined by its viscosity but also by the surface slip effects, which in the case of hydrophobic, atomically flat surfaces are crucially important.…”
Section: Nanoconfinement Effects On Watermentioning
confidence: 99%
“…Note that the diffusion of confined water in graphene nanochannel models is not isotropic in all three directions. However, following previous confinement studies, , we consider both lateral ( xy -plane) and perpendicular ( z -direction) self-diffusions of H 2 O for the total MSD. To avoid initial fluctuations only the last 100 ps trajectories are used for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…For H 2 O self-diffusion and O 2 diffusion, the pristine surface shows an overall higher diffusion coefficient than that of the defected surfaces with di-vacancy and N doping, as shown in Figures 4 and 5 respectively. Abbaspour et al 22 studied the transport of water confined inside two parallel graphene sheets using MD simulation with the NVT ensemble and SPC/E and Lennard-Jones potentials. They reported a slower motion of the confined molecules in the N-doped graphene case as well due to the stronger interaction between H 2 O and the N-doped atoms.…”
Section: Figure 6 H + Diffusion In 2d Confined Water As a Function Of...mentioning
confidence: 99%
“…Forming of these shapes has been also proved by molecular dynamics (MD) simulations under different temperatures, pressure, and CNT sizes. [6][7][8][9][10][11] Recently, some investigations reported that the conned water molecules show phase and shape transitions when experiencing electric or magnetic elds with different intensities in different directions. [12][13][14][15][16] For instance, Fu et al 12 studied the phase behavior of water conned in a CNT with the diameter of 1.2 nm under an external electric eld using MD simulations.…”
Section: Introductionmentioning
confidence: 99%